Avaliação do frescor e vida útil do camarão de água doce, Macrobrachium rosenbergii, armazenado em gelo - Kirschnik, Peter Gaberz [UNESP] (Universidade Estadual Paulista (Unesp), 2003)
The objective of the present work was to evaluate the shelf-life of the freshwater prawn Macrobrachium rosenbergii deheaded, shelled and stored in ice during 14 days. Two storage conditions were compared: DIC - prawn storage with direct ice contact and WIC - prawns without ice contact (specimens packed in polyethylene bags). The shelflife was evaluated by chemical analysis, namely: non-protein nitrogen (NPN), total volatile base nitrogen (TVB-N), rancidity (TBA), pH; and also by microbiological and sensorial analysis. Samples were collected at 0, 2, 4, 7, 10, and 14 days of storage. TVB-N initial contents (18.75 mg N/100g sample) reached 21.73 mg N/100g in WIC treatment and 5.47 mg N/100g in DIC treatment after 14 days of storage. NNP contents in WIC treatment increased from 436.99 mg N/100g at day zero to 542.30 mg N/100g in the end of storage. In DIC treatment, NNP contents decreased until the last day of this study (from 436.99 to 158.24 mg N/100g). TBA values increased in WIC treatment along of storage (from 0.08 to 1.83 mg of malonaldehyde/kg) and remained approximately constant in DIC treatment (from 0.08 mg to 0.18 of malonaldehyde/kg). Also for both treatments the pH was observed to remain constant during the whole storage time. Total and faecal coliforms countings were within the acceptable levels in both treatments. The initial psychrotrophic counting scored log 2.32 CFU/g for both experiments; at the end of the storage we observed an increase of about two logarithmic units/g for WIC treatment and of three logarithmic units/g for DIC treatment. Regarding the sensorial analysis, the assessors observed no changes in flavour until the 10th storage day for prawns in WIC treatment. At the 14th day, a decrease in quality (P < 0.05) was detected. In DIC treatment, however, flavour scores continuously decreased (P < 0.05) during the storage, reaching an average value of 4 in a scale from ...

Este trabalho teve como objetivo avaliar a vida útil do camarão de água doce Macrobrachium rosenbergii armazenado descabeçado em gelo durante 14 dias, comparando duas condições de armazenamento: CCG - camarões armazenados em contato direto com o gelo e SCG - sem contato com gelo (camarões em sacos plásticos mantidos em gelo). A vida útil foi monitorada por meio de análises químicas como nitrogênio não protéico (NNP), bases nitrogenadas voláteis (BNV), TBA, determinação do pH, e também por análises microbiológicas e sensoriais. Foram realizadas amostragens em intervalos de tempo aos 0, 2, 4, 7, 10 e 14 dias de estocagem. Os teores iniciais de BNV de 18,75 mg de N/100g de amostra atingiram 21,73 mg N/100g no tratamento SCG e 5,47 mg de N/100g no tratamento CCG após 14 dias de estocagem. Os teores de NNP para o tratamento SCG aumentaram de 436,99 mg de N/100g no dia zero para 542,30 mg de N/100g no final do armazenamento. No tratamento CCG, os teores de NNP diminuíram até o final do experimento (436,99 a 158,24 mg de N/100g). Os valores de TBA aumentaram no tratamento SCG ao longo da estocagem (0,08 a 1,83 mg de malonaldeído/kg) e mantiveram-se constantes no tratamento CCG (0,08 mg de malonaldeído/kg para 0,18 mg de malonaldeído/kg). Os dois tratamentos tiveram o mesmo comportamento quanto ao pH, mantendo-se constantes durante toda a estocagem. As contagens de coliformes fecais e totais mantiveram-se dentro dos níveis de aceitação em ambos os tratamentos. A contagem inicial de psicrotróficos foi de log 2,32 UFC/g para os dois experimentos, verificando-se, posteriormente um aumento de cerca de duas casas logarítmicas para o tratamento SCG e três unidades logarítmicas por grama de tecido para o tratamento CCG. Na análise sensorial os provadores não constataram alterações de sabor até o 10o dia de estocagem, nos camarões do tratamento SCG, detectando porém queda...
Keywords: Camarão de agua doce; Alimentos - Armazenamento; Alimentos - Consumo; Macrobrachium rosenbergii; Camarão - Deterioração; Shrimps